Correcting Parker Solar Probe Electron Measurements for Spacecraft Magnetic and Electric Fields. Issue 9 (17th September 2019) - McGinnis, Daniel; Halekas, Jasper; Whittlesey, Phyllis; Larson, Davin; Kasper, Justin
Abstract: The spacecraft body of the Parker Solar Probe may interfere with electron measurements in two ways. The first is the presence of several permanent magnets near the Solar Probe Analyzers (SPAN) instruments. The second is the widely varying spacecraft potential. We estimate the effect of these interferences by performing particle tracing simulations on electrons of various energies using a simplified model of the spacecraft potential and measurements of the magnetic fields. From this we can (1) estimate the individual and combined fields of view of the SPAN‐E instruments, (2) identify regions of phase space that may be highly distorted, and (3) simulate measurements of the velocity distribution function. We compute density, temperature, and bulk velocity moments of the measured distribution functions and find that a correction table derived from the particle tracing results can be incorporated in the computation to greatly decrease the errors caused by the spacecraft potential and magnetic fields. Similar tables could be computed for a wide range of spacecraft potentials and applied during the processing of actual SPAN data. Key Points: Spacecraft‐produced electrostatic and magnetic fields likely interfere with the collection of PSP SPAN‐E data These fields are modeled in order to estimate how electron measurements might be affected A technique for correcting electron measurements using these results is presented